MENINGKATKAN KEMAMPUAN MENULIS DENGAN MENGGUNAKAN MEDIA GAMBAR PADA MATERI TEKS LAPORAN OBSERVASI SISWA KELAS X - Yusrawati JR Simatupang (Master Bahasa, 2022)
This study aims to determine the increase in student writing skills through image media on text material report on class X observation results in MAN 3 Rukoh Banda Aceh. This research is a classroom action research, with stages of planning, actions, observations, and reflection. Research subjects for class X students totaling 27 students. Data collection techniques are carried out using documentation, observation and test techniques. The collected data is analyzed using qualitative descriptive techniques. The results showed that there was an increase in student learning outcomes after the implementation of image media on learning text writing observations, namely completeness in the first cycle of 62.96% with an average value of 66,11. Teacher skills managing Indonesian language learning using image media in the first cycle is categorized as good (70%), the activities of students in the first cycle are declared enough (54.28%). The completeness of student learning outcomes in the second cycle increased to 85.19% with an average value of 78.89 in the second cycle, the teacher activity in the second cycle increased became very good (90%), student activity in the second cycle increased to good (68, 57). Based on the results of the study it can be concluded that the image media can improve the ability to write the text of the observation of class X students in MAN 3 Rukoh Banda Aceh